THE PARAMETRIC EVALUATION OF ENVIRONMENTAL IMPACTS TO ANALYZE SITE PLAN IN ARCHITECTURE (CASE STUDY: CITY OF KHOY) - Mehrdad Azizia, Mahmood Rezaeib , Vahid Ghobadianc (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This article, by reviewing literature related to site analysis design processes and architecture theories, studies the Environmental Impact Analysis process in site analysis with a parametric approach. In other words, it is looking to answer the question of how we may employ modern computer approaches in the form of a parametric model to evaluate environmental factors that impact site plan analysis. This approach has not been yet investigate dusing this method and has only been analyzed and evaluated in the field of qualitative researches. In addition to understanding the effective factors in an urban environment, this paper tries to explain the role of physical elements in solving its problems. The goals of this study are gaining knowledge on effective environmental factors and characteristics of each one of them, determining the parameters that are effective in understanding these factors, and achieving a dynamic and digital solution for a parametric evaluation in site analysis. The paradigm used in this study, given its quantitative nature, will be the positivist paradigm. This research uses the quantitative approach and has been conducted by using computer simulations and modeling skills. The necessary inferences have been conducted through content analysis, Delphi method and desk review of documents. The findings of this paper demonstrate that in order to achieve success in the process of architecture designing in the present era, site analysis and design context should be placed in a creative, dynamic, and evaluated process and they should be employed through constructive and effective activities to creatively generate ideas in designing and to develop other design phases. In this condition, the great ability of digital applications is considered as an important and motivating factor for architects. An architect, with full knowledge and awareness regarding the issue of designing and designing tools, can breed creativity in the right direction and reach a completely scientific and logical conclusion in solving a design problem.